Characterization of cenosphere-reinforced vinyl ester composites. (March 2018) - Vimalathithan, PK; Vijayakumar, CT
Vinyl ester resin particulate composite plates having varying loading of cenosphere (150 µm) were fabricated using highly polished glass plates as moulds. The addition of cenosphere in the vinyl ester matrix has a significant effect on thermal, mechanical and dielectric properties. From the thermogravimetric analysis of the composites, one can infer that both the thermal degradation mechanism and the rate of thermal degradation are not affected by the incorporation of cenospheres in the vinyl ester resin, which can be credited both to the high thermal stability and the chemical inertness of cenospheres. The high specific strength and the probable uniform distribution of the cenospheres in the cured matrix are found to have an impact on the mechanical properties (tensile strength and flexural modulus) of the composites, with the optimum strength being observed when the loading of cenospheres in the matrix is 2–7% of weight proportion. The inhomogeneity between the cenosphere and the vinyl ester matrix can be related to the variation in the dielectric breakdown strength and dielectric constant of the composite.